U-Pb (zircon) age, petrology, and tectonic setting of the Canaan River pluton, southeastern New Brunswick, Canada - Johnson, Susan; Barr, Sandra M.; van Rooyen, Deanne; White, Chris E. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2018)
The Canaan River pluton comprises megacrystic monzogranite and quartz diorite to monzodiorite that is exposed in several small inliers on the Carboniferous New Brunswick Platform west of Moncton in southeastern New Brunswick. Its distinct geophysical signature and borehole data suggest that the Canaan River pluton is part of a large buried felsic to mafic intrusive body that lies at relatively shallow depths beneath flat-lying Pennsylvanian sandstone on the platform. New laser ablation ICP-MS in situ analysis of the megacrystic monzogranite yielded a U-Pb zircon concordia age of 412.6 ± 2.1 Ma, indicating that the intrusion is of Early Devonian (upper Lochkovian) age. The new radiometric data along with lithological, geochemical, and isotopic data suggest that the Canaan River pluton is most like the megacrystic Hawkshaw Granite of upper Lochkovian age in the Pokiok Batholith in southwestern New Brunswick. The similarities shown by these granites suggests that they may have been generated in the same complex tectonomagmatic setting related to the successive arrival of the leading edge of Ganderia and Avalonia at the composite Laurentian margin during the Salinic and Acadian orogenies.